ACCOUNTABILITY OF STATE FINANCES FOR THE USE OF THE HEALTH BUDGET AFTER THE COVID-19 PANDEMIC: ACCOUNTABILITY OF STATE FINANCES FOR THE USE OF THE HEALTH BUDGET AFTER THE COVID-19 PANDEMIC - Nurul Tarimana; Tri Suhendra Arbani; Ambowonua Nusantara (El-Iqthisadi, 2022)
The large number of health budgets that have not been spent by the relevant ministries and agencies is a problem in itself for various reasons. In the midst of the Covid-19 pandemic, several new regulations provide space in managing the Health budget without accountability, whereas it contradicts the spirit and principles of state finances. This can become a loophole in committing acts of corruption due to weak supervision and accountability. The purpose of this research is to build the concept and flexibility of accountability for the health budget in the midst of an emergency and to elaborate various regulations related to state financial accountability. This study uses normative legal research methods with a statutory approach in analyzing and providing future views regarding existing problems. The research results show regulatory loopholes that can be used in committing acts of corruption. Flexibility is meant by strengthening the supervision and budgeting side instead of the budget report. Due to various factors, reports are also an obstacle in itself when in a pandemic emergency. Keywords: Accountability, State Finances, Health Budget